Navigating institutional challenges in Mexico: The role of social capital in entrepreneurial families. Issue 1 (7th September 2018) - Estrada-Robles, Mariana; Williams, Nick; Vorley, Tim
Abstract : Purpose: Focusing on the family as the central unit of analysis, the purpose of this paper is to examine how entrepreneurial families, with more than one owner/entrepreneur, utilise social capital in a challenging institutional environment. Design/methodology/approach: The empirical focus of this paper is the institutional context of Mexico and how it impacts on entrepreneurial families and their access to social capital. The authors employ an in-depth qualitative approach to understand entrepreneurs' perspective as being part of an entrepreneurial family. A total of 36 semi-structured interviews were conducted with multiple respondents of each entrepreneurial family. Findings: This study shows that social capital allows members in the entrepreneurial family to access a wider pool of resources to utilise to benefit their ventures, while also helping them to operate in a challenging institutional environment. It also illustrates how social capital is used to overcome institutional asymmetries. Originality/value: This paper contributes to research by examining the links between institutions and entrepreneurial families through a focus on social capital. It provides a nuanced understanding of how the entrepreneurial family serves as an intermediary through which social capital gives family members access to resources and capabilities to enable their pursuit of entrepreneurial endeavours and overcome the institutional challenges they face in Mexico.